2021
DOI: 10.3390/healthcare9050540
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous Cystic Neoplasm of Pancreas in a Pregnant Woman Presenting with Severe Anemia and Gastric Bleeding: Case Report and Review of the Literature

Abstract: Mucinous cystic neoplasms of the pancreas are uncommon and especially their occurrence during pregnancy is an extremely rare event which necessitates an individualized and interdisciplinary management. A 33-year old woman was referred to our department during her third trimester of pregnancy (34th week of gestation) with severe anemia and tarry stools. Based on gastroscopic findings, our interdisciplinary team suspected a gastrointestinal stromal tumor and therefore indicated a prompt delivery via cesarean sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
2
0
2
Order By: Relevance
“…Their occurrence during pregnancy, though infrequent, has been documented in a limited number of case reports [1]. Notably, several studies have observed a rapid increase in the growth rate of MCNs during pregnancy [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their occurrence during pregnancy, though infrequent, has been documented in a limited number of case reports [1]. Notably, several studies have observed a rapid increase in the growth rate of MCNs during pregnancy [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…This rapid growth raises concerns about the potential for malignant transformation into invasive carcinomas, increased risk of pancreatitis, and other complications such as tumor rupture or fetal hazards like intrauterine growth restriction [6,7]. Although the direct impact of elevated pregnancy hormones on the malignant transformation of MCNs is not fully understood, Farahmandi et al reported a higher incidence of invasive carcinoma within MCNs during pregnancy compared to non-pregnant cases [4]. Additionally, progesterone has been suggested to play a protective role by potentially suppressing malignant transformation in the ovarian-like stroma of MCNs [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Während einer Schwangerschaft können MCN allerdings rasant an Größe zunehmen, was ein hormonabhängiges Wachstum nahelegt [4]. In der Literatur sind seit der Erstbeschreibung durch Smithers et al 1986 [10] 37 Fälle von schwangerschafts-assoziierten MCN beschrieben [11,12]. Diese waren im Durchschnitt größer als bei nicht-schwangeren Patienten (14,5 cm vs. 6,5 cm [13]) und wiesen häufiger invasive Karzinome auf (25,7 % vs. 3,9-16,3 % [14]) .…”
Section: Diskussionunclassified
“…Apesar de se identificar um estado hipoglicêmico (Hemoglicoteste com resultado de 22 mg/dL) inicial, a RN evolui satisfatoriamente, sem intercorrências, e recebeu alta em 6 dias após a internação. Especificamente o tumor de pâncreas, considerado insólito no período gestacional, pode resultar em outras complicações, modificações bioquímicas e consequências clínicas, como por exemplo anemia, além de apresentar sintomas inespecíficos, como dor abdominal leve, náuseas, vômitos, dor nas costas, dor sistêmica (FARAHMANDI et al, 2021). Portanto, é possível que as dores relatadas pela paciente tenham relação direta com a presença do tumor.…”
Section: Relato De Casounclassified